“Sem trabalho não sou nada”: capacidades estatais na política pública de trabalho : uma análise do Sistema Nacional de Emprego - SINE nas unidades federativas do Brasil, no período 2011-2018 - Leonardo Assis Martins Júnior (2024)
The work addresses the dimensions of state capacities within the scope of labor and income generation policies, focusing on the infrastructural and budgetary capacity of the National Employment System (Sine). The discussion unfolds in two main parts: first, a bibliographic and theoretical review of the concepts governing labor policy and its functioning is presented. This explanation is crucial given the scarcity of academic works specifically addressing the context of Sine's policy, thereby aiding in the understanding of this phenomenon. In the second part, a theoretical discussion on federalism, state capacity, and the mechanisms adopted by the national government to induce and coordinate the actions of subnational entities is conducted. Following this explanation, the federative units are analyzed using the Data Envelopment Analysis (DEA) methodology to evaluate their performance in relation to Sine during the period from 2011 to 2018, along with the created variable "Sine Placement Efficiency (ECS)," which allows for comparative analyses between states regarding their performance in labor intermediation policy. The frameworks proposed by Martins Júnior (2023), Wu et al. (2015), and Ramesh et al. (2016) will be used. The analyzed data is sourced from the General Register of Employed and Unemployed (Caged) and the Labor Intermediation Management Base (BG-IMO).